ANALYSIS OF THE RELATIONSHIP BETWEEN THE HEAD OF SECTION TO THE PERFORMANCE OF POPULATION CONTROL AND FAMILY PLANNING OFFICIALS IN LABUHAN BATU UTARA DISTRICT IN 2023 - Napitupulu, Erni Malinda; Herlina, Herlina; Widyaningsih, Fadlilah (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Health programs and projects are part of efforts to address health problems to improve public health status. The success of health programs and projects is greatly influenced by various factors, including good management in the management and control of a program. The aspect of sustainability in health development has a strategic role in continuing the benefits of health programs and continuing to provide the health services the community needs. The success of any organization in carrying out its various programs is highly dependent on leadership. Good leadership can support the achievement of productivity of employees and support staff within the organization and optimize various organizational functions. This study uses a quantitative approach, observational, cross-sectional design. The number of research samples was 52 respondents who were determined using a purposive sampling method. The instruments used as measuring tools are the Multifactor Leadership Questionnaire-5X (MLQ-5X) and the Individual Work Performance Assessment questionnaire. The research data will be analyzed using univariate and bivariate analysis to see broad descriptions and relationships between variables. There is a significant relationship between transformational leadership played by Heads of Division and improvement of individual employee performance in the aspect of Task Performance with a Pearson Chi-Square value of 22.26 4 and the value of p = 0.000* (p <0.05) So it can be concluded that the more dominant the application of transformational leadership, the better individual work performance in the aspect of carrying out their work tasks.